Implikasi Hukum Terhadap Pengajuan Perkawinan Beda Agama - Marta, Fakhirah; M.S., Edith Ratna (Notarius, 2025)
ABSTRACT                                                            Conventionally interfaith marriages are not regulated in detail in UU No. 1 of 1974 concerning Marriage. The aim of this research is to understand the consequences of Supreme Court Circular Letter Number 2 of 2023 on the sociological conditions of society on interfaith marriages in Indonesia and alternative recognition of interfaith marriages in Indonesia is the purpose of this research. The author conducts normative or theoretical research. The research results obtained are that SEMA Number 2 of 2023 does not allow judges to grant applications for interfaith marriages. Alternative recognition of interfaith marriages before the existence of SEMA Number 2 of 2023 was carried out by first submitting an application to the District Court or Religious Court to obtain a decision that legalizes interfaith marriages.Keywords: Legal Implication; Interfaith Marriage; Legal Implementation.ABSTRAKSejatinya Perkawinan beda agama tidak diatur secara rinci dalam Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan. Menegetahui Dampak Penerapan Surat Edaran Mahkamah Agung Nomor 2 Tahun 2023 terhadap kondisi sosiologis masyarakat atas perkawinan beda agama di Indonesia dan alternatif pengakuan atas perkawinan beda agama di Indonesia merupakan tujuan dalam penelitian ini. Penulis melakukan penelitian normatif atau teoritis. Hasil penelitian yang diperoleh yaitu bahwa SEMA Nomor 2 Tahun 2023 tidak meperbolehkan hakim untuk mengabulkan permohonan perkawinan beda agama. Alternatif pengakuan perkawinan beda agama sebelum adanya SEMA Nomor 2 Tahun 2023 dilakukan dengan terlebih dahulu mengajukan permohonan kepada Pengadilan Negeri dan/atau Pengadilan Agama untuk memperoleh putusan yang mengesahkan perkawinan beda agama.Katakunci: Implikasi Hukum; Perkawinan Beda Agama; Implementasi hukum.